PERAN MOBILE BANKING DAN KEUANGAN INKLUSI TERHADAP PENINGKATAN PROFITABILITAS PERBANKAN SYARIAH DI INDONESIA - Indriyani, Fany; Diah Fitri Astri Mastuti (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2021)
Study examined the factors that effect the using of mobile banking and financial inclusion as measured by the Financial Inclusion Index (IKI) on profitability as measured by Return on Assets (ROA) and Return on Equity (ROE) in Islamic Commercial Banks in Indonesia. The data for this study were obtained through a quantitative research with a sample of 12 Islamic Commercial Banks in Indonesia. The data involved a sample (n = 60) of twelve Islamic commercial bank during 5 years (2014-2018). The data were composed using linear regression and outcomes were presented by using software Eviews 10. The results show that partially mobile banking has a negative and significant effect on ROA and ROE, while the Financial Inclusion Index (IKI) has a negative and insignificant effect on ROA and ROE.